2021
DOI: 10.1007/s11604-021-01121-9
|View full text |Cite
|
Sign up to set email alerts
|

The utility of dynamic MRI in differentiating the hormone-producing ability of pituitary adenomas

Abstract: Purpose To investigate the relationship between dynamic magnetic resonance imaging (MRI) findings and hormonal activity in pituitary adenomas. Methods We retrospectively evaluated the dynamic MRI findings in 244 patients with pathologically confirmed pituitary adenomas and a diagnosis of clinically active prolactin (PRL)-producing adenomas. Among the 244 pituitary adenomas, 55, 16, 6, and 4 produced growth hormone (GH), PRL, adrenocorticotropic hormone, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Densely granulated tumors often have a weaker contrast enhancement than sparsely granulated tumors [ 83 ]. In a report examining the signal enhancement rate of PitNETs/pituitary adenomas relative to normal brain tissue (putamen) during the early (within 39 s) and delayed (195 s) phases of dynamic MRI, GH-producing tumors had lower contrast enhancement rates than other PitNETs/pituitary adenomas in both the early and delayed phases, suggesting that the signal enhancement rate on dynamic MRI may be a useful parameter for distinguishing GH-producing PitNETs/pituitary adenomas from other PitNETs/pituitary adenomas [ 84 ]. It has also been suggested that the signal enhancement curve of the tumor on dynamic MRI may be useful for diagnosis [ 85 , 86 ].…”
Section: Mri Diagnostic Strategies By Hormone Productionmentioning
confidence: 99%
“…Densely granulated tumors often have a weaker contrast enhancement than sparsely granulated tumors [ 83 ]. In a report examining the signal enhancement rate of PitNETs/pituitary adenomas relative to normal brain tissue (putamen) during the early (within 39 s) and delayed (195 s) phases of dynamic MRI, GH-producing tumors had lower contrast enhancement rates than other PitNETs/pituitary adenomas in both the early and delayed phases, suggesting that the signal enhancement rate on dynamic MRI may be a useful parameter for distinguishing GH-producing PitNETs/pituitary adenomas from other PitNETs/pituitary adenomas [ 84 ]. It has also been suggested that the signal enhancement curve of the tumor on dynamic MRI may be useful for diagnosis [ 85 , 86 ].…”
Section: Mri Diagnostic Strategies By Hormone Productionmentioning
confidence: 99%
“…We appreciate the interest of Dr. Mori et al in our article [1] and we have read their letter with great interest. As described in their letter, our methodology was limited in terms of spatial and temporal resolution, so in this study, we used early (EER) and delayed (DER) tumour-to-normal-tissue enhancement ratios.…”
Section: Dear Editormentioning
confidence: 80%
“…However, the subtypes cannot be evaluated preoperatively and can only be confirmed by histopathology after an operation. Besides, there are few reports on the comprehensive evaluation of GH pituitary adenomas by combining multiple MR features 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Besides, there are few reports on the comprehensive evaluation of GH pituitary adenomas by combining multiple MR features. 19,20 This study analyzed the value of multisequence MRI in predicting the subtypes of GH adenomas. Significant differences were found in tumor size, T2 signal intensity, T2 rSI, enhancement degree, and invasiveness between DG and SG adenomas.…”
Section: Discussionmentioning
confidence: 99%